2018
DOI: 10.1590/2318-0331.231820170178
|View full text |Cite
|
Sign up to set email alerts
|

Different approaches to estimate the sediment yield in a tropical watershed

Abstract: Several Sediment Delivery Ratio (SDR) models have been used to estimate Sediment Yield (SY), mainly in data-scarce and ungauged basins, such as in many regions of Brazil. However, it is difficult to choose the most suitable SDR model, mainly because of the lack of investigations of this approach using observed data. Here, we investigated the performance of five widely used SDR models (SDREST) to estimate sediment yield values (SYEST ) based on observed data in a tropical watershed. We used observed sediment yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…We found a SDR value of approximately 5% in the Córrego Água Azul catchment. This value has the same order of magnitude of the SDR (6.1%) found in a similar catchment in terms of annual sediment yield [3] and is similar to the values (5.5-10.5%) observed in a tropical catchment inside the same biome in Brazil [57]. De Vente, Poesen, Verstraeten, Rompaey and Govers [4] also reported studies in catchments with areas between 30-1000 km 2 and sediment yield (around 100 Mg yr −1 ) that also show SDR values smaller than 10%, indicating that our study area has a small SDR value; considering that the authors found values greater than 50% in some basins.…”
Section: Sediment Delivery Ratio (Sdr)supporting
confidence: 86%
“…We found a SDR value of approximately 5% in the Córrego Água Azul catchment. This value has the same order of magnitude of the SDR (6.1%) found in a similar catchment in terms of annual sediment yield [3] and is similar to the values (5.5-10.5%) observed in a tropical catchment inside the same biome in Brazil [57]. De Vente, Poesen, Verstraeten, Rompaey and Govers [4] also reported studies in catchments with areas between 30-1000 km 2 and sediment yield (around 100 Mg yr −1 ) that also show SDR values smaller than 10%, indicating that our study area has a small SDR value; considering that the authors found values greater than 50% in some basins.…”
Section: Sediment Delivery Ratio (Sdr)supporting
confidence: 86%
“…In the Almas River basin in Goiás, the average sediment production was 0.0088 metric ton (t) per day (d −1 ) per km 2 ranging from 0.0027 to 0.0548 t d −1 per km 2 , the greatest variations and sediment production were observed in agricultural areas with agriculture and pasture, exposed soil and steeper areas [7]. Another study reported that in the Guariroba River basin in Mato Grosso do Sul, sediment production increased in the larger drainage area and in steeper areas of the basin; thus, the sediment production in this tropical basin with predominance of pasture and planted forest varied from 0.0331 to 0.0482 t d −1 per km 2 [37].…”
Section: Discussionmentioning
confidence: 94%
“…The wet season starts in October and ends in May while the dry season runs from June to September. Further information about the Guariroba river basin can be found in Colman et al (2018), Almagro et al (2019), Sone et al (2019). In this case, we measured hydraulic data and the bed sediment particle size between 2017 and 2019 of three sections of the Guariroba river with distinct characteristics using ADCP (Riversurveyor Model M9, Sontek) and BLM-84 sampler for bed loads, among others (Supplementary Table S11 -http://abesdn.org.br/wp-content/uploads/2021/04/SupplementaryFIle_atualizado.pdf).…”
Section: Case Study and Nhss Computational Tool Verificationmentioning
confidence: 99%